2018
DOI: 10.4103/apc.apc_117_17
|View full text |Cite
|
Sign up to set email alerts
|

Simulation training improves team dynamics and performance in a low-resource cardiac intensive care unit

Abstract: Introduction:Although simulation training has been utilized quite extensively in highincome medical environments, its feasibility and effect on team performance in lowresource pediatric Cardiac Intensive Care Unit (CICU) environments has not been demonstrated. We hypothesized that lowfidelity simulationbased crisis resource management training would lead to improvements in team performance in such settings.Methods:In this prospective observational study, the effect of simulation on team dynamics and performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…A possible reason for the variation in knowledge and skills described above may be due to different teaching methods used in low resource settings, where students receive large amounts of didactic teaching focused on lectures, assignments and examinations (Sivaram et al, 2018). In such settings, there is often less focus on the development of critical thinking skills and the hands-on skills needed to assess and manage patients.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for the variation in knowledge and skills described above may be due to different teaching methods used in low resource settings, where students receive large amounts of didactic teaching focused on lectures, assignments and examinations (Sivaram et al, 2018). In such settings, there is often less focus on the development of critical thinking skills and the hands-on skills needed to assess and manage patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, a state-of-the art intervention will make use of digital options by translating the training material into an app [39, 40]. Previous research has shown that patient coaching can be an intervention to improve communication [4951], and professionals can also significantly benefit [52, 53].…”
Section: Introductionmentioning
confidence: 99%
“…3 Pediatric cardiac critical care simulation research has shown that this educational modality can improve the knowledge levels, teamwork, communication, and self-reported comfort and confidence in caring for CICU patients by physicians, advanced practice providers (APPs), and bedside staff. [4][5][6][7][8] Simulation boot camps for critical care and cardiology fellows and APPs have been reported. 5,[9][10][11] These courses lead to improvement in overall CICU knowledge and confidence when managing these complex patients.…”
Section: The Role Of Simulation In Cardiac Intensive Care Educationmentioning
confidence: 99%
“…Several publications have recommended curricula and learning objectives for pediatric cardiac critical care; however, few have described the different modalities from which educators can choose to teach these complex topic. [1][2][3][4] At the 14th Annual International Meeting of the Pediatric Cardiac Intensive Care Society (PCICS), the authors presented a simulation workshop for junior multidisciplinary providers focused on cardiopulmonary interactions as subject matter.…”
mentioning
confidence: 99%
See 1 more Smart Citation